2018
DOI: 10.4103/aer.aer_113_18
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of intravenous magnesium sulfate versus intravenous paracetamol on children posttonsillectomy pain and analgesic requirement: A randomized controlled study

Abstract: Background:One of the most common complications of tonsillectomy is pain, which leading to delayed recovery and later hospital discharge.Aims:We intended to compare the efficacy of magnesium sulfate versus paracetamol on the posttonsillectomy pain and analgesic requirement.Settings and Design:This study design was a prospective randomized controlled double-blinded clinical study.Patients and Methods:A total of 60 children with the American Society of Anesthesiologists physical status classes I and II, aged 3–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Magnesium sulfate also showed optimal analgesic efficacy in the present study. Hamed and Al-Saeed [16] assessed the efficacy of intravenous magnesium sulfate versus intravenous paracetamol on pain in children after tonsillectomy and the need for analgesics. They evaluated 60 children between 3 to 12 years in two groups of magnesium sulfate and paracetamol infusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium sulfate also showed optimal analgesic efficacy in the present study. Hamed and Al-Saeed [16] assessed the efficacy of intravenous magnesium sulfate versus intravenous paracetamol on pain in children after tonsillectomy and the need for analgesics. They evaluated 60 children between 3 to 12 years in two groups of magnesium sulfate and paracetamol infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Mostafa et al [15] evaluated the prophylactic effect of intravenous infusion of magnesium on postoperative sore throat after thyroid surgery and reported that it significantly decreased the incidence and severity of sore throat after thyroidectomy. Hamed and Al-Saeed [16] assessed the efficacy of intravenous magnesium sulfate versus intravenous paracetamol on pain in children after tonsillectomy and the need for analgesics and reported that magnesium sulfate had superior analgesic efficacy compared with paracetamol, and decreased the need for analgesics. However, Kalani et al [12] compared the analgesic effects of paracetamol and magnesium sulfate on pain during surgery and found that although administration of narcotics decreased by the use of paracetamol and magnesium sulfate, this reduction was not significant.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Recently, the use of magnesium sulfate in reducing postoperative pain has been studied. 12 Lidocaine is one of the antiarrhythmic drugs and its main mechanism of action is blocking voltage-gated Na + channels that inhibit the activity of the upper laryngeal nerve and reduces the long-term blockage of the glottis. It is used locally (in the area of the tonsils) or intravenously to prevent laryngospasm, but it may reduce the seizure threshold.…”
Section: Ethical Publication Statementmentioning
confidence: 99%
“…2 Postoperative pain control after the tonsillectomy has a very important role in recovery time, hospitalization duration, hemodynamic effects, bleeding, nausea, vomiting, and financial costs. 12 Recently, the use of magnesium sulfate in reducing postoperative pain has been studied. 12 Lidocaine is one of the antiarrhythmic drugs and its main mechanism of action is blocking voltage-gated Na + channels that inhibit the activity of the upper laryngeal nerve and reduces the long-term blockage of the glottis.…”
mentioning
confidence: 99%
See 1 more Smart Citation